Nineteenth century glass manufacture and its effect on photographic glass stability. Issue 2 (3rd May 2020) - Brostoff, Lynn; Zaleski, Stephanie; Ward-Bamford, Carol Lynn; Montagnino, Elizabeth; Muller, Isabelle; Buechele, Andrew; Loew, Murray; France, Fenella
Abstract: The Industrial Revolution led to mass production of many materials that naturally found their way into nineteenth century cultural heritage. One such material is flat glass, the manufacture of which underwent a succession of innovations that influenced the burgeoning field of photography. Results of historical research illustrate how changes in the glass industry contributed to the diversity of glass available to nineteenth century photographers either as cover glass in enclosures or as substrates. This information provides important context for limited surveys of nineteenth century photographic glass in two historical society collections using only microscopy and X-ray fluorescence (XRF). Survey results, plus microscopy, XRF, and OCT and analysis of historical and artificially aged model glass, provide new evidence about instability in glass in historical collections of photography, and underscore the potential for any type of nineteenth century glass to undergo progressive deterioration involving attack on the silicate network in adverse microclimates. Results have implications for both prioritisation of collection needs and conservation practices.